Analyze of Communication Processes in State Border Guard College - Indriksons, Alens; Ļubkina, Velta; Ušča, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Communication is the activity of delivering information through the exchange of thoughts, messages or information. The most popular type of communication in militarized educational institution is downward communication. State Border Guard College is militarized educational institution with hierarchy, discipline and one way communication. The predominant educational approach is the classical pedagogy. But a system, where pedagogue only transfers information and the student – receives it, could not be called as independent-personality developing. The aim of this research is to find out students thoughts of ongoing communication processes in State Border Guard College. For this purpose was carried out the survey. The result was processed by the data processing programs and performed content analysis. For the improvement of Border Guard training system were drawn conclusions.